Menikah Lebih dari Empat Perempuan dalam Perspektif Hukum Keluarga Islam - Mhd. Sufi’y; A. Kumedi Ja’far (CV. Creative Tugu Pena, 2024)
This paper discusses the concept of marrying more than four women in the perspective of Islamic family law. Islam sets a limit on the maximum number of wives that a man can marry, namely four, as stipulated in the Qur'an Surah An-Nisa verse 3. Polygamy in Islam is allowed under certain conditions, one of which is the husband's ability to be fair to his wives. However, marrying more than four women is not allowed and is against Islamic law. The discussion in this paper includes an analysis of the Shari'ah fundamentals governing polygamy, the wisdom behind limiting the number of wives, and the implementation of Islamic family law in various Muslim countries, including Indonesia. In addition, the paper highlights the importance of justice in polygamy as a key requirement, and the legal consequences for violating this rule. The conclusion that can be drawn is that marrying more than four women is not permitted in Islam, and this prohibition aims to maintain justice and welfare in domestic life. It also provides protection for women's rights and prevents injustices that may arise in the practice of excessive polygamy.